PLANT GROWTH STIMULATION BvLIGNITE HuMICAcios. PART-I. EFFECT OF AMMONIUM HUMATE ON THE GRO\VTH OF WHEAT (Biological Sciences - PJSIR, 2002)
) Humicacids were prepared by nitric acid oxidation of Lakhracoal. The product  was alkali  soluble polymeric  material  having an aromatic characteristic. Ammonium salt of the h umicsubstances was prepared to find out  itseffects  in  the presence and absence of N-fertilizer on the yield of wheat, biological yield of whole plant and number  of tillers associated with the plants. The addition of ammonia salt of humicacids increased the size of grain, plant and leaves. The small dose of 0.5 kgha·1alone and in  combination  with half dose of N-fertilizer  (60 kg ha·1is the optimum dose of growth  stimulationof wheat  in  Sindh. It suggests  that the agricultural  soil of experimental  site is rich in humousmaterial.